Silencing of matrix metalloprotease-12 delays the progression of castration-resistant prostate cancer by regulating autophagy and lipolysis - Xiaoyu Zheng; Xiaoqin Xie; Wei Wang; Liang Wang; Bing Tan (Brazilian Journal of Medical and Biological Research, 2024)
Abstract The complex pathogenesis of castration-resistant prostate cancer (CRPC) makes it challenging to identify effective treatment methods. Matrix metalloproteinase (MMP)-12 can degrade elastin as well as various extracellular matrix (ECM) components, which is associated with cancer progression. However, the relationship between MMP-12 and CRPC progression is poorly understood. In this study, we observed the effect of MMP-12 on the progression of CRPC and further explored its potential mechanism of action. High levels of MMP-12 were observed in patients with CRPC. We therefore developed cell co-culture and mouse models to study the function of MMP-12. Silencing MMP-12 in CRPC cells disrupted lipid utilization and autophagy marker expression via the CD36/CPT1 and P62/LC3 pathways, respectively, leading to reduced CRPC cell migration and invasion. Moreover, animal experiments confirmed that MMP-12-knockdown CRPC xenograft tumors exhibited reduced tumor growth, and the mechanisms involved the promotion of cancer cell autophagy and the inhibition of lipid catabolism. According to our results, MMP-12 played important roles in the progression of CRPC by disrupting adipocyte maturation and regulating cancer migration and invasion via the modulation of autophagy and lipid catabolism pathways.